POST-SOCIALISTS TRANSFORMATION AND CHANGES OF VALUE ORIENTATIONS: ECONOMIC LIBERALISM AND MARKET FUNDAMENTALISM - Janković, Aleksandar B. (Politeia, 2021)
The aim of this paper is to investigate the intensity and dispersion of value orientations of economic liberalism and market fundamentalism among young people in Bosnia and Herzegovina on two historic occasions – in the period immediately before the collapse of the Communist social order (1989) and in the period of post-Communist transformation, more precisely over the period of consolidating the neoliberal pattern of economic regulation following the  impact of financial and economic crisis (2012). An analysis of empirical data will discover to what extent social consciousness, expressed in the form of value orientations, follows structural social changes that take place due to the establishing of neoliberal model of capitalistic regulation. In terms of theoretical background, the analysis relies on the theory of value-normative dissonance. The analysis of empirical data is executed by means of result comparison method of value orientations sum scales where such an analysis is possible, while in other cases a simpler method of pattern descriptive analysis is performed, along with comparison of individual items. The data used was collected in the respective survey entitled ‘Social Structure and Quality of Life’, conducted in 1989 in all the republics of the former Yugoslavia, and ‘Value Orientation and Attitude Towards Social Changes’, conducted in 2012 in the Doboj region of Bosnia and Herzegovina.
Keywords: Value orientations; economic liberalism; market; fundamentalism; youth; Bosnia and Herzegovina